Tetrabutylammonium Bifluoride as an Efficient Activating Agent for Copper-Catalyzed Vinylsilane Cross-Coupling Reactions - Cornelissen, Loïc; Nagy, Audric; Leyssens, Tom; Riant, Olivier (Synlett, 2017)
Vinylsilanes are versatile and efficient nucleophiles in cross-coupling reactions. Herein is described the use of tetrabutylammonium bifluoride as a mild, cheap and scalable activating agent in several copper-catalyzed vinylsilane cross-couplings.
Keywords: vinylsilane; copper; cross-coupling; activating agent; catalysis